Mechanical and microstructural improvements of high-strength lightweight concrete with carbon nanotubes and shale-based aggregates - Qiansha Li; Jin Chai Lee; Wei Chek Moon; Jing Lin Ng; Zeety Md Yusof; Xiaojiang Hong; Qian He; Bo Li (Discover Applied Sciences)
Abstract High-strength lightweight concrete (HSLWC) is increasingly needed in modern architectural structures. However, conventional HSLWC is brittle and has a low tensile strength. This study investigated the possibility of combining multiwalled carbon nanotubes (MWCNTs) with shale pottery sand (SPC) and shale ceramsite (SC) to improve the mechanical characteristics and microstructure of HSLWC. Workability, mechanical properties (compressive strength under different curing regimes, splitting tensile strength, modulus of elasticity, flexural strength, slump and density), and microstructure were assessed for six different MWCNT contents (0%, 0.02%, 0.05%, 0.1%, 0.15%, and 0.2%, by cement weight). The findings indicated that the slump decreases as the MWCNT concentration increases, whereas all the mixtures maintain densities within the lightweight concrete range. At a carbon nanotube content of 0.1%, the compressive strength, splitting tensile strength, elastic modulus, and flexural strength of the 28-day high-strength, low-density concrete increase by 25.34%, 31.25%, 22.83%, and 46.83%, respectively, compared with those of the concrete without MWCNTs. The optimal curing condition was determined to be 7 days. Furthermore, the incorporation of a superplasticizer and shrinkage-reducing admixture helps maintain the lightweight properties of the concrete while ensuring structural integrity. Scanning electron microscopy analysis revealed that carbon nanotubes effectively bridge microcracks, reinforce weak areas, and impede microcrack propagation. This synergistic approach of combining carbon nanotubes with SC and SPC represents a novel strategy for enhancing the performance of high-strength, low-density concrete, improving the mechanical properties of lightweight concrete, and optimizing the dispersion of carbon nanotubes, thereby facilitating broader technical applications.